Host Genetics But Not Commensal Microbiota Determines the Initial Development of Systemic Autoimmune Disease in BXD2 Mice. Issue 4 (10th February 2022) - Hong, Huixian; Alduraibi, Fatima; Ponder, David; Duck, Wayne L.; Morrow, Casey D.; Foote, Jeremy B.; Schoeb, Trenton R.; Fatima, Huma; Elson, Charles O.; Hsu, Hui‐Chen; Mountz, John D.
Abstract : Objective: To determine the extent to which the gut microbiome influences systemic autoimmunity in a mouse model of lupus. Methods: We generated germ‐free (GF) lupus‐prone BXD2 mice, which under normal conditions develop spontaneous germinal centers (GCs) and high titers of serum autoantibodies. GF status was confirmed by gut bacterial culture. The autoimmune phenotypes of 6‐ and 12‐month‐old gnotobiotic GF BXD2 mice and specific pathogen–free (SPF) BXD2 mice were compared. Serum levels of autoantibodies were measured by enzyme‐linked immunosorbent assay. Histologic sections of the mouse kidney and joints were evaluated. Flow cytometry was used to analyze GCs and age‐associated B cells. CD4+ T cells were analyzed for PD‐1+ICOS+ activated T cells, T follicular regulatory (Tfr) cells (Foxp3+CD25+ PD‐1+CXCR5+), and PD‐1+ICOS+ T cells expressing interleukin‐17A (IL‐17A) or interferon‐γ (IFNγ) after stimulation with phorbol myristate acetate (PMA)/ionomycin. Results: In 6‐month‐old mice, GF status did not affect splenomegaly, GC B cells, age‐associated B cells, or serum autoantibody levels, except for IgG antihistone. GF BXD2 mice exhibited a significantly higher percentage of Tfr cells compared to their SPF counterparts ( P < 0.05). At 12 months of age, however, GF BXD2 mice had significantly diminished IgG autoantibody levels and a lower percentage of GC B cells and age‐associated B cells ( P < 0.05). Following stimulation with PMA/ionomycin, PD‐1+ICOS+ CD4+ T cells expressed significantly lower IL‐17A, but not IFNγ, levels in GF BXD2 mice compared to SPF BXD2 mice ( P < 0.01). SPF BXD2 mice and GF BXD2 mice developed equivalent renal and joint disease with no significant differences in severity. Conclusion: Our results suggest a model in which genetics plays a dominant role in determining the initial development of autoimmunity. In contrast, gut microbiomes may regulate the persistence of certain aspects of systemic autoimmunity.